2014
DOI: 10.1194/jlr.m043851
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 is a novel regulator of metabolic function in skeletal muscle

Abstract: This article is available online at http://www.jlr.org breast cancer and/or tumorigenesis in reproductive tissues ( 3 ). The BRCA1 gene produces either a full-length breast cancer type 1 susceptibility protein (BRCA1) or through alternatively splicing two documented variants, BRCA1 ⌬ 11 or BRCA1 ⌬ 11b, both of which lack a nuclear localization signal ( 4 ). Recently, BRCA1 was identifi ed as a regulator of lipid metabolism in human breast cancer cells (MCF7) as a result of direct interaction with the phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 56 publications
1
29
3
Order By: Relevance
“…A similar energy balance mechanism may link prolonged sedentary bouts with reduced BRCA1 expression. BRCA1 is a key regulator of metabolism; by binding to the inactive form of Acetyl-CoA Carboxylase (ACCA), BRCA1 reduces the rate of long-chain fatty acid synthesis (51,52). Thus, lipoprotein lipase and BRCA1 play complementary roles in response to increased energy needs: lipoprotein lipase breaks down fats and BRCA1 reduces their synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…A similar energy balance mechanism may link prolonged sedentary bouts with reduced BRCA1 expression. BRCA1 is a key regulator of metabolism; by binding to the inactive form of Acetyl-CoA Carboxylase (ACCA), BRCA1 reduces the rate of long-chain fatty acid synthesis (51,52). Thus, lipoprotein lipase and BRCA1 play complementary roles in response to increased energy needs: lipoprotein lipase breaks down fats and BRCA1 reduces their synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that Brca1 is expressed in skeletal muscle and is a critical regulator of metabolic function in cultured human myotubes (5). Specifically, we found that in vitro knockdown of Brca1 expression resulted in reduced mitochondrial O 2 consumption in these cells (5).…”
mentioning
confidence: 99%
“…We recently demonstrated that Brca1 is expressed in skeletal muscle and is a critical regulator of metabolic function in cultured human myotubes (5). Specifically, we found that in vitro knockdown of Brca1 expression resulted in reduced mitochondrial O 2 consumption in these cells (5). Others have shown that overexpression of Brca1 in cultured MCF7 cells, a breast cancer cell line, increased oxidative gene expression, whereas loss of Brca1 expression increased glycolytic gene expression (6).…”
mentioning
confidence: 99%
“…In fact, little is known about BRCA1’s role in metabolism in normal tissue. In cardiomyocytes, loss of BRCA1 has been reported to reduce glucose levels and fatty acid oxidation (36) and in skeletal muscle, BRCA1 loss reduces fatty acid synthesis (37). Menendez and colleagues use targeted metabolomics to show that breast epithelial cells transfected with a BRCA1 mutation (185delAG) undergo metabolic reprograming to increase anabolic processes, including the tricarboxylic acid (TCA) cycle and lipogenesis (38).…”
Section: Discussionmentioning
confidence: 99%